Systematization of the Simulation Process of Transformer Inrush Current Using EMTP - Hun-Chul Seo; Gi-Hyeon Gwon (Applied Sciences, 2019)
An inrush current is generated when a transformer is energized. This current has a large magnitude and rich harmonics, thereby causing mal-operation of the protection relay. Therefore, the development of countermeasures against inrush current is necessary, and this study has been performed by computer simulations. However, it is difficult for a power system operator to perform a computer simulation as it is difficult to determine what data should be selected and entered. Therefore, this paper establishes the simulation process of transformer inrush current using the Electromagnetic Transients Program (EMTP). Two methods to simulate the transformer inrush current are described in detail. Based on the actual 154 kV transformer test report in Korea, the simulation results of the inrush current using the two methods are discussed.